La gestación en medio de la inseguridad alimentaria: percepciones de un grupo de adolescentes embarazadas (2014)
ABSTRACT: Describing pregnant adolescents’ perceptions regarding food insecurity in their households Method Quantitative methodology involving an ethnographic approach was used; seventeen adolescents in their third trimester of pregnancy were included in the study; they were registered in the Medellin public hospital network’s prenatal control program and living in households classified as being food insecure. Results Some adolescents said that initially their pregnancies were unwanted; however, feeling a baby in their wombs became an act of love and became acceptance of their unborn children. Single-parent families headed by women and a background of adolescent pregnancy amongst the participants’ mothers were striking findings. Although pregnant adolescents recognized the type of nutrition which should have been consumed according to their physiological period, beliefs and preferences, their financial difficulties and the situation that they lived in limited their access to food, thereby making the most valuable food in nutritional terms become the least consumed by them. Conclusions Poverty spreads the experience of food insecurity and hunger within a household and generates concern in mothers-to-be about the future of their unborn children’s nutrition, feelings of intense pain, helplessness and hopelessness concerning the future.